The Concept of Analogy in the Qur'an: Hudan Representation in IT Perspective (Information Technology) - Khotimatul Maulidah (Saniya Institute, 2024)
The Qur'an encompasses a wide range of knowledge, including the Qur'anic proverbs found in its text. These proverbs of the Qur'an offer concise and eloquent expressions, making abstract ideas accessible and relatable. The proverbs of the Qur'an become valuable lessons for those who wish to learn them. In today's modern world, the proverbs of the Qur'an can be utilized through information technology (IT) to explain various concepts in the Qur'an, one of which is the concept of hudan (guidance). This research is a qualitative study using library research. The approach used is the interpretation and analogy approach. First, the concept of hudan in the Qur'an has various meanings, depending on the context of the verse that explains it. When divided into several forms, the concept of hudan in the Qur'an is divided into forms, such as; classification of hudan, level of hudan, criteria for people who get hudan, and causes of obstruction for someone to get hudan. Second, the concept of hudan in the Qur'an if analogized in the context of IT media (information technology), it can be likened to the use of washing machines in the context of; functions and objectives, operationalization, and causes of not running optimally.